Using Circle Game to Improve Students’ Vocabulary Mastery of the Eighth Grade Students - Ferayanti; Usman, Sriati; Mashuri; Aminah (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study aims to determine the effectiveness of the circle game in improving the vocabulary mastery of eighth-grade students at SMP Labschool Untad Palu. The background of this study is the low mastery of English vocabulary among students, which affects their ability in four basic English skills. The researcher applied the circle game as an engaging learning strategy to overcome this issue. The research employed a pre-experimental design with one group pre-test and post-test. The sample consisted of 19 students from class VIII. The research instrument was a vocabulary test in the form of multiple-choice questions, administered before and after the treatment. The findings showed that the students’ vocabulary mastery significantly improved after the implementation of the circle game. The average score of the pre-test was 60.35, while the post-test average rose to 78.60. The gain score was 18.25. Based on the paired sample t-test result, the significance value was 0.000, which is lower than the standard alpha value of 0.05. This means that the improvement is statistically significant. These findings prove that the use of the circle game has a positive impact on students’ vocabulary acquisition. In addition to the quantitative results, qualitative observations indicated that students were more enthusiastic, confident, and active during the learning process. The atmosphere in the classroom became more dynamic and supportive, which encouraged students to participate and use English vocabulary in a fun and relaxed way.